Evaluation of strategies for improving the transgene expression in an oleaginous microalga Scenedesmus acutus - Anongpat Suttangkakul; Anchalee Sirikhachornkit; Piyada Juntawong; Wilasinee Puangtame; Thitikorn Chomtong; Suchada Srifa; Sukhita Sathitnaitham; Wasawat Dumrongthawatchai; Kanidtha Jariyachawalid; Supachai Vuttipongchaikij (BMC Biotechnology, 2019)
Abstract Background Genetic transformation of microalgae has been hampered by inefficient transgene expression, limiting the progress of microalgal biotechnology. Many vector tools and strategies have been developed in recent years to improve transgene expression in the model microalga Chlamydomonas, but these were hardly applied to other microalgae. In this work, naturally-isolated oleaginous microalgae were accessed for genetic transformation, and various expression systems were evaluated in a selected microalga to circumvent inefficient transgene expression. Results Initially, a strain of Scenedesmus acutus was selected from the oleaginous microalgal collection based on its highest transformation rate and transgene stability. This strain, which had very low or no GFP reporter expression, was first tested to improve transgene expression by using intron-containing constructs and the transcript fusion using ble::E2A. The intron-containing constructs yielded 2.5–7.5% of transformants with 2–4-fold fluorescence signals, while the majority of the transformants of the transcript fusion had the fluorescence signals up to 10-fold. Subsequently, three UV-induced S. acutus mutants were isolated with moderate increases in the level and frequency of transgene expression (2–3-fold and 10–12%, respectively). Finally, a transcript fusion system was developed using psy white mutants with an expression vector containing PSY::E2A for complementation and light selection. Transformants with green colonies were selected under light exposure, and the transgene expression was detected at protein levels. Although the improvement using PSY::E2A was only minor (1–2-fold increase and ~ 7% of transformants), this system provides an alternative selectable marker that is compatible with large-scale culture. Conclusions Here, the overall improvement of transgene expression using the Chlamydomonas tools was moderate. The most effective tool so far is the transcript fusion using ble::E2A system. This work demonstrates that, so far, genetic engineering of non-model microalgae is still a challenging task. Further development of tools and strategies for transgene expression in microalgae are critically needed.